2018
DOI: 10.1111/nmo.13436
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and perinatal stress and irritable bowel syndrome in young adults – A nationwide register‐based cohort study

Abstract: In this large population-based study, we found that mode of delivery was associated with an increased risk for IBS in young adulthood, while other proxies for pre- and perinatal stress were not. Female gender remains the most important risk factor for IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The amount of premature births is increasing, and for the babies that survive, there is an increased risk of disability and neuropsychological disorders [ 9 ]. On the other hand, a Swedish nationwide register-based cohort study found preterm birth to be associated with a decreased risk for IBS among young adults [ 10 ]. However, since the maturation of a fetus’ different organ systems occur at unique paces (time periods), a difference of one gestational week could lead to significantly different future health problems [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of premature births is increasing, and for the babies that survive, there is an increased risk of disability and neuropsychological disorders [ 9 ]. On the other hand, a Swedish nationwide register-based cohort study found preterm birth to be associated with a decreased risk for IBS among young adults [ 10 ]. However, since the maturation of a fetus’ different organ systems occur at unique paces (time periods), a difference of one gestational week could lead to significantly different future health problems [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results further strengthen the concept that appropriate manipulation of the gut microbiome during adolescence, may reduce the probability of developing severe disorders that could affect the gut and the CNS later. This is all the more interesting in view of the worldwide increasing incidence of functional gastrointestinal disorders affecting the adolescent and young population [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…The present study used a much more robust process to determine whether a subject had IBS according to international criteria or a previous medical diagnosis, compared to the previous study, which had simply asked if a subject had “diarrhoea, constipation, and painful abdominal distension,” which were then attributed to IBS. Others have also sought to reproduce the original report of an association between birth weight and IBS, however, despite a study of approximately 2 000 000 Swedish subjects no association was found 23,24 . It therefore seems very unlikely that there is an association between low birth weight and IBS, when the latter is accurately measured.…”
Section: Discussionmentioning
confidence: 99%
“…Age at the time of survey in years (mean, SD) 56.0 (13.9) an association between birth weight and IBS, however, despite a study of approximately 2 000 000 Swedish subjects no association was found. 23,24 It therefore seems very unlikely that there is an association between low birth weight and IBS, when the latter is accurately measured.…”
Section: Demographic Variable N (%)mentioning
confidence: 99%